2013
DOI: 10.1063/1.4801526
|View full text |Cite
|
Sign up to set email alerts
|

Ion acceleration from laser-driven electrostatic shocks

Abstract: Multi-dimensional particle-in-cell simulations are used to study the generation of electrostatic shocks in plasma and the reflection of background ions to produce high-quality and high-energy ion beams. Electrostatic shocks are driven by the interaction of two plasmas with different density and/or relative drift velocity. The energy and number of ions reflected by the shock increase with increasing density ratio and relative drift velocity between the two interacting plasmas. It is shown that the interaction o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(150 citation statements)
references
References 38 publications
(61 reference statements)
10
139
1
Order By: Relevance
“…Such scaling allows us to project that 170-MeV low-energy spread proton beams can be obtained at a CO 2 laser intensity of ~10 18 W/cm 2 , attainable at 100TW peak power (a 0 =10). Recently reported simulations [26] support this expectation. Different physical mechanisms are being explored with the objective of accessing high-peak-power THzradiation sources desirable for emerging applications ranging from material studies, to work for Homeland Security.…”
Section: Science Opportunitiessupporting
confidence: 73%
“…Such scaling allows us to project that 170-MeV low-energy spread proton beams can be obtained at a CO 2 laser intensity of ~10 18 W/cm 2 , attainable at 100TW peak power (a 0 =10). Recently reported simulations [26] support this expectation. Different physical mechanisms are being explored with the objective of accessing high-peak-power THzradiation sources desirable for emerging applications ranging from material studies, to work for Homeland Security.…”
Section: Science Opportunitiessupporting
confidence: 73%
“…We have followed the field evolution in 2D and 3D simulations and showed that a quasi-steady-state value is reached, with the magnetic field being generated only in the downstream region, in contrary to electromagnetic shocks where the filamentation instability creates a magnetic field across the shock front. We have observed that since the field is generated in the downstream region, the effect of the selfgenerated magnetic field on the formation process is negligible, and the properties of the electrostatic shock, e.g., in terms of ion reflection, are preserved [7,8,42]. On the other hand, the strong field in the downstream region influences the dynamics of the particles in this region, and it can lead to distinct signatures of the shock.…”
Section: -2mentioning
confidence: 95%
“…The new applications pose now new challenges to our understanding of collisionless shocks structure and their potential to accelerate particles [4][5][6][7][8][9][10] . Microscopically, strong shocks can be supported by suitable plasma waves that randomize particle trajectories in lieu of binary collisions.…”
Section: Introductionmentioning
confidence: 99%